Quick & clever drawing - Sanders, Michael , 1950- (David & Charles Book, 2009)
Offers an introduction to drawing. This work shares the author's many inventive and foolproof drawing techniques with many art materials - developed from years of teaching both beginners and improvers. Each chapter explores how to draw a popular subject, starting with art technique - focused exercises before moving on to a step-by-step drawing.